Air Quality Assessment Based on Real-Time Continuous Monitoring: Particulate and Nitrogen Dioxide Concentrations in South Tangerang - Ihsan, Iif Miftahul; Ma'rufatin, Anies; Zahroh, Nyayu Fatimah; Ikhsan, Iik Nurul; Suwedi, Nawa; Pratama, Reba Anindyajati; Adhi, Rizky Pratama; Handika, Rendi; Lusia, Akira; Nishihashi, Masahide; Terao, Yukio; Hashimoto, Shigeru; Nara, Hideki; Mukai, Hitoshi (BRIN Publishing (Penerbit BRIN), 2025)
The increasing concentration of PM2.5, PM10, and NO2 in urban areas will impact human health. Measuring and calculating the concentration of PM2.5, PM10, and NO2 is one of the efforts to control pollution because it can obtain information on the status or category of these air pollutants. Therefore, this study aims to analyze air quality, including PM2.5, PM10, and NO2 particulates calculated based on the Air Quality Index. Pollutant measurements are carried out continuously and in real-time for 24 hours. Pollutant measurements use a continuous dichotomous aerosol chemical speciation analyzer (ACSA-14) tool placed in the BJ Habibie Science and Technology Area, Serpong, South Tangerang. Analysis of PM2.5, PM10, and NO2 concentrations were analyzed to obtain the average daily concentration during the measurement period and the ISPU method was regulated in the Regulation of the Minister of Environment and Forestry Number 14 of 2020. During the measurement period, the daily average concentrations of PM2.5, PM10, and NO2 were 40.0 μg/m3, 60.4 μg/m3, and 37.4 μg/m3, respectively, with the highest concentrations of 170.8 μg/m3, 336.0 μg/m3, 647.5 μg/m3. The moderate and unhealthy categories dominated the results of the ISPU PM2.5 analysis during the measurement period, respectively, at 55.5% and 23.0%. The good and moderate categories dominate the ISPU PM10 and NO2 analysis results, namely 38.0% and 52.2% for PM10 and 82.5% and 7.5% for NO2, respectively.